(The Characterization of Sweet Potato Flour) - Reno Fitri Hasrini; H G Pohan; Tita Aviana (Warta Industri Hasil Pertanian, 2011)
Research on the improvement of sweet potato flour processing and characterization of the product had been conducted .the aims of this research was to reduce the enzymatic reactions for sweet potato with the improvement of flour processing,and to characterrize of the product .the steps of this research were include (1) the processing of flour by immersed of raw materials in warm water drying at temperature 50,60,70 oc (2)proximiate analysis of the product including moisture ,ash,protein,fat,crude fiber ,carbohydrate content and energy value (3)analysis and characterization of their physicochemical including yields,speeds of drying,viscosity ,the microscopic of starch granule ,white degree value and gel strenght the results showed that flour had low a maximum viscosity, the shapes of their granule were polygonal circles ,ovals and their size were varied .from this research it shown that immersed that immersed of raw carbohydrste content and energy value ,9,03% : 2,27%: 13,6 :0,44%: 0,99%< 74,7% dan 375 cal/100 g respectively key eord sweet potato ,enzymatic browing reaction ,viscosity ,whitenes .